Association of immunoglobulin GM allotypes with longevity in long-living individuals from Southern Italy - Annibale A. Puca; Anna Ferrario; Anna Maciag; Giulia Accardi; Anna Aiello; Caterina Maria Gambino; Giuseppina Candore; Calogero Caruso; Aryan M. Namboodiri; Janardan P. Pandey (Immunity & Ageing, 2018)
Abstract Background The aim of this study was to analyse the role of GM allotypes, i.e. the hereditary antigenic determinants expressed on immunoglobulin polypeptide chains, in the attainment of longevity. The role played by immunoglobulin allotypes in the control of immune responses is well known as well as the role of an efficient immune response in longevity achievement. So, it is conceivable that particular GM allotypes may contribute to the generation of an efficient immune response that supports successful ageing, hence longevity. Methods In order to show if GM allotypes play a role in the achievement of longevity, we typed the DNA of 95 Long-living individuals (LLIs) and 96 young control individuals (YCs) from South Italy for GM3/17 and GM23+/− alleles. Results To demonstrate the role of GM allotypes in the attainment of longevity we compared genotype and allele frequencies of GM allotypes between LLIs and YCs. A global chi-square test (3 × 2) shows that the distribution of genotypes at the GM 3/17 locus is highly significantly different in LLIs from that observed in YCs (p < 0.0001). The 2 × 2 chi-square test shows that the carriers of the GM3 allele contribute to this highly significant difference. Accordingly, GM3 allele is significantly overrepresented in LLIs. No significant differences were instead observed regarding GM23 allele. Conclusion These preliminary results show that GM3 allotype is significantly overrepresented in LLIs. To best of our knowledge, this is the first study performed to assess the role of GM allotypes in longevity. So, it should be necessary to verify the data in a larger sample of individuals to confirm GM role in the attainment of longevity.